Analysis of The Performance of Microbubble Generators as Aerators in Tilapia Cultivation with High Density Fishery Systems - Pambudiarto, Benny Arif; Pahlawan, Ilham Arifin; Fatmawati, Yuni; Mirbath, Muhammad Shobichul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Fish farmers in Gresik Regency face significant challenges in developing aquaculture, including land conversion and extended dry seasons that lead to pond drought. Microbubble generators (MBGs) present a potential solution to these issues. This study evaluates the effectiveness of different MBG types in tilapia farming. Weekly measurements of fish mass and length were conducted to determine growth rates using direct methods. Water quality was assessed by testing COD and ammonia levels at the Gresik Regency DLH Laboratory and measuring dissolved oxygen levels directly with a DO meter. The distribution and size of the bubbles were analyzed using the shadow image technique, supported by MATLAB software. The study employed a stocking density of 100 fish/mÂ² with three treatments: MBG swirl type, venturi type, and a conventional aerator. The findings revealed that the MBG swirl type resulted in the best fish growth and maintained water quality within the required standards. The specific growth rate in swirl-type ponds was 3.970 Â± 0.014, with a survival rate of 100%. Additionally, the swirl-type MBG effectively maintained dissolved oxygen levels above 3 ppm, meeting the minimum requirement for fish survival, despite having less optimal microbubble distribution compared to the venturi type. While the MBG venturi type performed well initially, technical issues affected its bubble consistency over time. Enhancements in the venturi MBG's design are recommended to improve its performance and reliability.